2003
DOI: 10.1177/0020872803046001590
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas of Israeli social workers

Abstract: The purpose of this study was to ascertain how Israeli social workers make ethical decisions. Areas studied included types of ethical dilemmas encountered by social workers, the decisions they made, their education and training in ethics, knowledge and use of the Israel Association's code of ethics, the systems that support staff decision-making in ethical dilemmas and demographic characteristics. One of the anticipated outcomes was the need to educate future social workers to identify and resolve ethical dile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…The importance of values in social work is indisputable, for values represent a fundamental working element in social work practice and ethics (Bartlett, 1958;Gordon, 1965;Linzer, 1999;Loewenberg & Dolgoff, 1992). Social work values embody social workers' preferred views of people, what they prefer for people, and how they work with people (Levy, 1973).…”
Section: Social Work Valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of values in social work is indisputable, for values represent a fundamental working element in social work practice and ethics (Bartlett, 1958;Gordon, 1965;Linzer, 1999;Loewenberg & Dolgoff, 1992). Social work values embody social workers' preferred views of people, what they prefer for people, and how they work with people (Levy, 1973).…”
Section: Social Work Valuesmentioning
confidence: 99%
“…Should the social worker validate Mr. C's wish not to become an American citizen, or should the social worker persuade him otherwise? Linzer (1992Linzer ( , 1999 has demonstrated that Levy's values classification model (discussed below) is indicated for analyzing social work values, as well as the values of each party to a conflict. Levy's (1973) model begins at the most abstract level (i.e., preferred conceptions of people), and develops toward defining more concrete preferences (i.e., outcomes and instrumentalities for working with people).…”
Section: Values Conflictmentioning
confidence: 99%
See 2 more Smart Citations
“…Research findings (Lonne et al, 2004) have shown that emerging ethical issues affecting practice reported by managers and practitioners in public and non-profit agencies included changed accountabilities away from service users toward employing organizations and funders as well as the negative impact of resource constraints on quality service delivery. According to Linzer et al (2003) the main ethical dilemmas that social workers encountered were related to: confidentiality; their duty to warn about and prevent harm; number of client contacts; competence of practitioner; informed consent; 2 truth telling or not when it might cause harm to the client. Musil et al (2004) in a review of relevant literature came to the conclusion that social work service workers follow two kinds of patterns of dealing with dilemmas.…”
mentioning
confidence: 99%